2008
DOI: 10.1016/j.nucmedbio.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Coligand effects on the solution stability, biodistribution and metabolism of the 99mTc-labeled cyclic RGDfK tetramer

Abstract: In this study, we present the evaluation of two new ternary ligand 99m Tc complexes [ 99m Tc(HYNICtetramer)(tricine)(L)] (L = ISONIC and PDA) as potential radiotracers for tumor imaging. The athymic nude mice bearing the MDA-MB-435 human breast cancer xenografts were used to evaluate their biodistribution and metabolic properties. The solution stability data showed that [ 99m Tc (HYNIC-tetramer)(tricine)(L)] (L = ISONIC and PDA) had a significant (14% and 35%, respectively) at 6 h in the absence of excess ISON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 53 publications
(88 reference statements)
0
50
0
Order By: Relevance
“…Over the last several years, we have been using a ternary ligand system (HYNIC, tricine and TPPTS) (Figure 1 A : HYNIC = 6-hydrazinonicotinyl; TPPTS = trisodium triphenylphosphine-3,3′,3″-trisulfonate) for 99m Tc-labeling of small biomolecules (BMs), which include chemotactic peptides and LTB 4 receptor antagonists for imaging infection and inflammation, 1, 2 integrin α v β 3 receptor antagonists for tumor imaging, 37 and GPIIb/IIIa receptor antagonists for imaging thrombus. 810 This ternary ligand system forms complexes [ 99m Tc(HYNIC-BM)(tricine)(TPPTS)] (Figure 1 A : BM = peptide and non-peptide receptor ligand) with extremely high specific activity.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several years, we have been using a ternary ligand system (HYNIC, tricine and TPPTS) (Figure 1 A : HYNIC = 6-hydrazinonicotinyl; TPPTS = trisodium triphenylphosphine-3,3′,3″-trisulfonate) for 99m Tc-labeling of small biomolecules (BMs), which include chemotactic peptides and LTB 4 receptor antagonists for imaging infection and inflammation, 1, 2 integrin α v β 3 receptor antagonists for tumor imaging, 37 and GPIIb/IIIa receptor antagonists for imaging thrombus. 810 This ternary ligand system forms complexes [ 99m Tc(HYNIC-BM)(tricine)(TPPTS)] (Figure 1 A : BM = peptide and non-peptide receptor ligand) with extremely high specific activity.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that multimerization of cyclic RGD peptides enhances their integrin α v β 3 binding affinity and improves the radiotracer tumor uptake. However, the kidney and liver uptake of radiolabeled cyclic RGD peptides was also increased significantly as the peptide multiplicity increases 47,5761…”
Section: Introductionmentioning
confidence: 99%
“…Tricine/trisodium triphenylphosphine-3,39,3$-trisulfonate was used as a coligand and reductant in the radiolabeling protocol. The whole procedure was rapid and efficient, with a high labeling yield, consistent with the convenient formulation of a labeling kit (31). Moreover, 99m Tc-HYNIC-H6F exhibited excellent in vitro stability in saline for 6 h (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 57%